Population structure of Tabapua beef cattle using pedigree analysis - Bernardes, P. A. [UNESP]; Grossi, D. A. [UNESP]; Savegnago, R. P. [UNESP]; Buzanskas, M. E. [UNESP]; Ramos, S. B. [UNESP]; Romanzini, E. P. [UNESP]; Guidolin, D. G. F.; Bezerra, L. A. F.; Lobo, R. B.; Munari, D. P. [UNESP] (Elsevier B.V., 2016)
This study evaluated a Tabapua population structure and the linear relationship of the inbreeding coefficient with phenotypic values of weaning weight adjusted to 210 days of age (W210); age at first calving (AFC); first (CI1), second (CI2) and average (ACI) calving intervals; and, accumulated productivity (ACP). The phenotypic data used were from 7340 cows and the pedigree file had 15,241 animals. The average pedigree completeness of the last six generations was 47.99%. The effective numbers of founders and ancestors were 124 and 110, respectively, with a ratio of 1.13. These results suggested the absence of the genetic bottleneck effect. The inbreeding coefficient increased over generations and the average was 0.007. The effective population size became small in the last generation. The regression analysis results of phenotypic values for inbreeding coefficients were not significant (P > 0.05) for W210, CI1 and ACP; and, significant (P < 0.05) and favorable for AFC, ACI and CI2. The results indicated that mating between related animals and the intensive use of few breeders should be avoided. Regression analysis indicated no inbreeding depression, which can be justified by the fact that inbreeding is not yet strongly established. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Effective number of founders; Effective population size; Inbreeding; Pedigree completeness